Indonesian Self-Risk Assessment for Cervical Cancer (SiNara): Instrument Development and Validation - Madiuw, Devita; Hermayanti, Yanti; Solehati, Tetti (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Women’s ignorance of cervical cancer risk factors has caused low participation in the screening of the disease. Women can independently assess cervical cancer risk factors in themselves through a risk assessment instrument. However, no instruments were found that assessed cervical cancer risk based on the characteristics of Indonesian women.Purpose: This study aimed to develop and validate an Indonesian self-risk instrument for cervical cancer.Methods: The instrument was developed based on scale development following the guidelines by DeVellis (2017). A cross-sectional study was implemented to validate the instrument. A total of 20 women were involved in the pre-testing, and as many as 200 women were included in the instrument testing. Based on the scale development guidelines, data collection was initiated with a literature review to determine the instrument construct and item pool. A total of 29 articles were used in the formulation of the item pool and resulted in 38 items for validity and reliability testing. Content validity ratio (CVR) and content validity index (CVI) were used to test the content validity of the instrument, which was reviewed by three experts. Exploratory factor analysis (EFA) with principal component analysis (PCA) method and Kuder-Richardson 20 (KR-20) were used to evaluate construct validity and internal consistency reliability, respectively.Results: A total of 26 items met the content validity and 21 items met the construct validity evaluation, with five items being removed because they had a loading factor value of <0.4. After the validity were evaluated, the instrument was reduced from 38 items to 21 items. The internal consistency reliability with Kuder-Richardson 20 (KR-20) was 0.807.Conclusion: The Indonesian self-risk assessment for cervical cancer (SiNara) instrument is of good validity and reliability. However, it needs to be tested in other settings using larger samples to measure its psychometric properties as well as its applicability and acceptability.